Analisis Kritik Marxisme dalam Cerpen Semilyar ikan Memakan anjing-anjing dan Pabrik Skripsi Pada Antologi Cerpen Kompas 2014 - Annisa Aprilia Haque; Lia Camellia; Nur’afiah Fauziah; Seli Mauludani (Universitas Muhammadiyah Jember, 2026)
This study aims to reveal how short stories can represent social criticism related to class inequality in society, and aims to describe the forms of class conflict, social oppression, and class consciousness depicted in two short stories entitled